Persepsi Masyarakat terhadap Calon Kepala Daerah Perempuan (Perspektif Sosiologi Gender dalam Pilkada NTB 2024) - Huldiya Syamsiar; Abdul Latif; Abdurrohman Abdurrohman (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2025)
Public awareness of gender equality in the Pilkada is not only a matter of candidate electability, but also part of a long struggle to change social norms that limit women. This study aims to explore public perceptions of female regional head candidates in the 2024 NTB Regional Elections, with a Gender Sociology approach namely focusing on the study of gender roles, relationships and inequality that emphasizes the dynamics of the relationship between gender and politics. This study uses a qualitative research method with a phenomenological approach. The data collection techniques used are observation and interviews. The data analysis used in this study is data analysis from Milles and Huberman which consists of data reduction, data presentation, and drawing conclusions. The results of the study show that there are various public perceptions related to the first female regional head candidate, there are perceptions that are influenced by the norms culture and religi of the NTB community which is predominantly Muslim and has strong traditions Where the Patriarchal culture is still dominant in the way women are viewed in the political realm is still very careful. Second, perceptions about leadership skills, some people think that women are considered less able to face major challenges in government, which emphasizes physical strength and assertiveness. Third, public awareness of gender equality shows doubt that women have the same capacity as men to lead. Fourth, there is a perception that political party support and candidate popularity, political parties that support female candidates with clear visions and relevant programs can increase the credibility and attractiveness of these candidates in the eyes of voters.